Financial Inclusion Strategies: A Bibliometric Study of Microfinance and Economic Development Initiatives - Loso Judijanto; Eva Yuniarti Utami; Tera Lesmana (West Science Interdisciplinary Studies, 2024)
Financial inclusion, crucial for equitable economic development, remains a pivotal focus area in global development discourse. Microfinance, an essential component of financial inclusion strategies, aims to provide financial services to marginalized communities, thereby fostering economic empowerment. This study conducts a comprehensive bibliometric analysis of the scholarly literature on microfinance and economic development initiatives. By systematically reviewing and synthesizing a vast array of academic publications, including journal articles, conference proceedings, and book chapters, this study identifies key themes, trends, and research gaps in the field. The analysis encompasses publication trends, citation patterns, thematic clusters, author collaboration networks, and emerging research directions. Findings highlight the evolution of microfinance from its origins to its contemporary applications, with a shift in research emphasis from theoretical underpinnings to practical implementations and regional applications. Moreover, the study identifies underexplored research avenues, such as the role of education in financial inclusion, the impact of microcredit services in specific regions, and regulatory environments for small and medium-sized enterprises. The author collaboration network reveals both robust collaborative clusters and opportunities for new collaborations, reflecting the dynamic and interconnected nature of scholarly engagement in this domain. Ultimately, this study informs evidence-based policy formulation, program design, and academic inquiry, contributing to more effective and sustainable interventions aimed at promoting financial inclusion and fostering economic growth on a global scale.